How does the PEN Program Affect the Sustainability of MSMEs: A Case Study in Bantul - Nur Andriyani; Huda Kurnia Maulana; Annisa Nur Salam; Frisca Marta Utami; Alivia Nabila Kinasih; Syarif Ardiansyah; Iskandar Iskandar (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
The Indonesian economy has faced a pandemic for the last two years. The Covid-19 pandemic is the starting point for implementing digital technology for MSMEs. MSMEs and the government maintain the sustainability of MSMEs, which are one of the pillars of the economy. This study aims to analyze the impact of digital technology implementation, human capital and PEN program in maintaining business sustainability directly or through competitive advantage. The object of research is culinary MSMEs in Bantul Yogyakarta Regency. SEM PLS is employed to estimate the primary data by using WARPS PLS 6.0 application. The results revealed that digital technology variables could directly affect business sustainability. Meanwhile, human capital and the PEN program affect business sustainability through competitive advantage. The results suggest government extend the fiscal stimulus.